2016
DOI: 10.1111/jvh.12647
|View full text |Cite
|
Sign up to set email alerts
|

The association between hepatitis B self‐awareness and depression: Exploring the modifying effects of socio‐economic factors

Abstract: China has a high prevalence of HBV. Despite previous studies, uncertainty remains about the association of HBV with depression. This study explores the strength of the association and the modifying effects of participants' self-awareness of the disease and their socio-economic status. Data from the baseline of a Chinese cohort study of approximately 500 000 adults were analysed. Depression was assessed using the Composite International Diagnostic Inventory. Blood spot tests were conducted to detect hepatitis B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…However, these findings may be confounded by social stigma. For patients who had CHB but were unaware of their status, there was no statistically significant difference in having major depression . Although development of mental illness may be attributable, at least in part, to discrimination or fear of discrimination, this perception carries significant consequences for patients with CHB …”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 93%
See 3 more Smart Citations
“…However, these findings may be confounded by social stigma. For patients who had CHB but were unaware of their status, there was no statistically significant difference in having major depression . Although development of mental illness may be attributable, at least in part, to discrimination or fear of discrimination, this perception carries significant consequences for patients with CHB …”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 93%
“…In a related study, Zhu et al found that the higher the Child‐Pugh rating, the higher patients scored on two widely used depression and anxiety scales (Hamilton Depression Scale and Hamilton Anxiety Scale). In another China‐based study, controlled for socioeconomic factors, awareness of having hepatitis B increased odds of major depression (OR 1.84 [95% CI: 1.16‐2.90]) compared with patients without hepatitis B . However, these findings may be confounded by social stigma.…”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 99%
See 2 more Smart Citations
“…So we choose the Zipf's second law to get the threshold n of high frequency words. Zipf's second law is a very important law in bibliometrics [5]. The predecessors have proposed the critical value calculation formula of high-frequency words and low-frequency words according to Zipf's second law,which is,…”
Section: Figure 3 the Knowledge Map By Searching All Literature Keywomentioning
confidence: 99%